2018
DOI: 10.1021/acscatal.8b00394
|View full text |Cite
|
Sign up to set email alerts
|

Buffer-Induced Acceleration and Inhibition in Polyoxometalate-Catalyzed Organophosphorus Ester Hydrolysis

Abstract: The Zr-containing polyoxometalates (POMs), including (Et2NH2)8{[α-PW11O39Zr­(μ–OH)­(H2O)]2}·7H2O (1), effectively catalyze the hydrolysis of nerve agent simulants at near-neutral pH. Analogous Zr-containing heterogeneous systems are much-studied and effective nerve-agent hydrolysis catalysts, but due to their heterogeneous nature, it is very challenging to know the exact structure of the catalytic sites during turnover and to clarify at the molecular level the elementary mechanistic processes. Here, under homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…The absence of hydrolysis might be due to the presence of precipitation which was observed under both these pH conditions and which probably resulted in the loss of Hf1-WD2 catalyst (see Figure S1). In addition, the presence of different buffers might also contribute to the observed changes in the reactivity, similarly to the recently reported inhibition and activation effect of buffers on the catalytic activity of Zr-POMs (Collins-Wildman et al, 2018).…”
Section: Resultssupporting
confidence: 77%
“…The absence of hydrolysis might be due to the presence of precipitation which was observed under both these pH conditions and which probably resulted in the loss of Hf1-WD2 catalyst (see Figure S1). In addition, the presence of different buffers might also contribute to the observed changes in the reactivity, similarly to the recently reported inhibition and activation effect of buffers on the catalytic activity of Zr-POMs (Collins-Wildman et al, 2018).…”
Section: Resultssupporting
confidence: 77%
“…Solutions of transferrin (7.5 µM) was incubated with each Zr-substituted POM (7.5 mM) in phosphate buffer (10 mM, pH 7.4) at 60 °C over the course of a week. Although previous studies have shown that phosphate buffer may impact POM reactivity [ 37 ], it ensures pH stability and pH conditions which are pertinent to physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions of transferrin (7.5 µM) was incubated with each Zr-substituted POM (7.5 mM) in phosphate buffer (10 mM, pH 7.4) at 60 °C over the course of a week. Although previous studies have shown that phosphate buffer may impact POM reactivity [37], it ensures pH stability and pH conditions which are pertinent to physiological conditions. Aliquots of the reaction mixture were taken at different time intervals and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) on separate gels for each Zr-POM by plotting the different time increments next to each other (Figures S1-S6).…”
Section: Hydrolysis Of Transferrin By Zr-substituted Pomsmentioning
confidence: 99%
“…A stepwise disappearance of the singlet corresponding to the substrate DMNP and gradual appearance of a singlet attributed to the hydrolysis side product dimethyl phosphate (DMP) can be observed ( Figure 3 ). 28 The corrected rate constant after subtracting the rate constant obtained from reaction mixtures lacking the POM catalyst ( k uncat = 4.01 (±0.10) × 10 –5 min –1 ) - under elsewise identical reaction conditions considering autohydrolysis of the substrate - gives a value of k corr = 2.42 (±0.10) × 10 –4 min –1 ( Figure S17 ) which is about seven times higher than the values obtained for the uncatalyzed reaction ( k uncat = 4.01 (±0.10) × 10 –5 min –1 ) and control experiments containing the [GeW 10 O 36 ] 8– precursor ( k corr = 3.37 (±0.12) × 10 –5 min –1 ) ( Figure S18 ), respectively. Concentration dependent experiments on the phosphoesterase activity of [Ce(H 2 O) 3 (GeW 10 ) 2 ] 9– and [Zr(H 2 O) 3 (GeW 10 ) 2 ] 8– toward NPP and DMNP were carried out, and the substrate conversion for a specific reaction time (45.6 h, 49 h, and 25 h) under varying catalyst concentrations (0.5 mM, 1.0 mM, 1.25 mM, 2.5 mM) was recorded and compared ( Table S20 ).…”
Section: Resultsmentioning
confidence: 99%